1992
DOI: 10.1182/blood.v79.7.1746.1746
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD7-CD57+ T cells: a new T-lymphocyte subset expanded during human immunodeficiency virus infection

Abstract: CD7 and CD57 are two cell surface molecules related to the differentiation or functional stages of CD4+ T cells. The CD4+CD7- T cells represent a minor subset of CD4+ cells in normal individuals and are considered to contain the normal counterpart of Sezary T cells; the CD4+CD57+ peripheral blood lymphocytes (PBL) are detectable in long- term renal allograft recipients. We compared the cell surface expression of these CD7 and CD57 markers on CD4+ T lymphocytes in peripheral blood and lymphoid organs from norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…Their proportions in the peripheral blood also increase in patients with colorectal cancer [6,7]. CD57 þ T cells reportedly increase in patients with AIDS [8,9] and those subjected to kidney, heart and bone marrow (BM) transplantation [10][11][12]. It is suggested that these T cells with NK cell markers may be counterparts of extrathymic T cells in mice [13], which have intermediate T cell receptor (TCR) (a major proportion also have NK cell marker, NK1.1), and contain potentially self-minor lymphocyte stimulatory (Mls) antigen-reactive clones [14,15] and thereby may play a role in inducing autoimmune diseases [14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…Their proportions in the peripheral blood also increase in patients with colorectal cancer [6,7]. CD57 þ T cells reportedly increase in patients with AIDS [8,9] and those subjected to kidney, heart and bone marrow (BM) transplantation [10][11][12]. It is suggested that these T cells with NK cell markers may be counterparts of extrathymic T cells in mice [13], which have intermediate T cell receptor (TCR) (a major proportion also have NK cell marker, NK1.1), and contain potentially self-minor lymphocyte stimulatory (Mls) antigen-reactive clones [14,15] and thereby may play a role in inducing autoimmune diseases [14][15][16].…”
Section: Introductionmentioning
confidence: 95%
“…First, antibody cross-linking of CD7 induces an increase in intracellular calcium [ 131. Second, various studies have demonstrated both inhibitory and stimulatory effects of CD7-specific mAb on the proliferation and cytokine response of both a@+ Tcells and y/6+ Tcells [14-191. Furthermore, changes in CD7 expression on T cells or T cell subsets have been reported in various disease states, including HIV infection [20] and rheumatoid arthritis [21]. CD7 has also recently been implicated as a potential cofactor in syncytium formation induced by HIV-1 [22].…”
Section: [I 132681mentioning
confidence: 99%
“…Indeed, both genes share similar promoter regions and exonic organization (60). Although most human peripheral CD4 + T cells are CD7 + , several immunodeficiency states including HIV infection (61,62), allogeneic bone marrow transplantation (63), and immunosenescence (64) are associated with the expansion of CD4 + CD7 -T cells reminiscent of the increase in CD4 + CD90cells in MAIDS. Further investigations are required to determine whether cAMP is indeed involved in the human CD4 + CD7phenotype and whether PKA type I antagonists can be considered as potential therapeutic agents in these diseases.…”
Section: Discussionmentioning
confidence: 99%